(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Many Arabic learning strategies have been used to improve speaking skills. However, it turns out that not every learning strategy has succeeded in increasing speaking skills. This paper aims to understand (1) the contribution of using Arabic as the language of instruction, (2) the process of increasing student’s speaking skills after attending lectures using Arabic as an introduction, and (3) analyzing efforts to improve the quality of lectures. So far, this aspect has not been paid attention to in existing studies. This research approach is qualitative with a case study model. The research data is collected through interviews, observation, and documentation methods. Data analysis starts from data collection, data description, and data reduction, then verification in detail. The results showed that students benefited from using Arabic as the language of instruction, namely the addition of new vocabulary and terms, mastery of sentence structures, and the courage to express themselves in Arabic. Improving speaking skills is characterized by increased self-confidence, fluency in speaking, and more information to support speaking skills. The need to improve the quality of lectures by squeezing and the leader motivates the lecturers to use Arabic as the language of instruction, provides many opportunities for students to be active, and Arabicization of linguistic terms is needed. The conclusion is that Arabic as an introduction to lectures can improve students’ speaking skills. This article provides suggestions on the effective use of Arabic as a strategy for learning speaking skills.